Mastering Scientific and Medical Writing A Self-help Guide - Rogers, Silvia M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This self-help guide is intended for scientists and medical professionals and students who wish to improve their scientific writing skills. Exercises invite the reader to practice the most important aspects of scientific writing. Although the book addresses certain issues more troublesome to scientific communicators of a non-English language origin, the guide will be of equal benefit to those whose first language is English. If you want not only to write but to write well, this book is for you. This second edition takes into account new developments in the area of scientific communication. In particular, the importance of authenticity is addressed, drawing attention to the sensitive issue of plagiarism in scientific texts.
Introduction -- Good versus Poor Scientific Writing: an orientation -- Words and Units: orthography and Punctuation -- Forming Sentences: grammar -- Putting it Nicely: Style -- Redundancy and Jargon: Focusing on the essentials -- Quoting Published Material: Reference Formats -- Avoiding Discrimination: ethics of Scientific Writing -- Sticking to your word: Plagiarism -- Structuring Scientific Texts: getting the (3z(BStory(3y (Bout.s
Keywords: Medicine; Medicine & Public Health; Medicine/Public Health, general